2011
DOI: 10.1111/j.1365-2966.2011.19134.x
|View full text |Cite
|
Sign up to set email alerts
|

The shape of dark matter haloes in the Aquarius simulations: evolution and memory

Abstract: We use the high‐resolution cosmological N‐body simulations from the Aquarius project to investigate in detail the mechanisms that determine the shape of Milky Way type dark matter haloes. We find that, when measured at the instantaneous virial radius, the shape of individual haloes changes with time, evolving from a typically prolate configuration at early stages to a more triaxial/oblate geometry at the present day. This evolution in halo shape correlates well with the distribution of the infalling material: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
193
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(216 citation statements)
references
References 113 publications
(154 reference statements)
22
193
0
Order By: Relevance
“…This supports the idea that the DM elongation at high redshifts, soon after the assembly, is induced by the preferred direction of the large-scale structure. This is compatible with the results of Vera-Ciro et al (2011), who showed using DM-only simulations that at high redshift, when haloes are fed through narrow filaments, prolateness dominates. The shape of the haloes changes to a more oblate configuration at lower redshift, when the accretion becomes more isotropic.…”
Section: Origin Of Halo Elongationsupporting
confidence: 92%
“…This supports the idea that the DM elongation at high redshifts, soon after the assembly, is induced by the preferred direction of the large-scale structure. This is compatible with the results of Vera-Ciro et al (2011), who showed using DM-only simulations that at high redshift, when haloes are fed through narrow filaments, prolateness dominates. The shape of the haloes changes to a more oblate configuration at lower redshift, when the accretion becomes more isotropic.…”
Section: Origin Of Halo Elongationsupporting
confidence: 92%
“…The shape of the halo is unknown, but is here assumed to be spherical. There have been studies showing that the dark-matter halo might be highly oblate or prolate (e.g., Amorisco & Bertin 2010;Vera-Ciro et al 2011). This would further increase σ z .…”
Section: Uncertainties and Assumptionsmentioning
confidence: 99%
“…After this time, material was fed into the halo of Aq-D mainly via a secondary filament, oriented nearly perpendicular to the primary filament that dominates the local large-scale structure. Vera-Ciro et al (2011) find that the dark matter halo of Aq-D changes its orientation owing to the change in infall direction. This change in infall direction is likely the main reason why no rotation signal is detected in the mock GC systems around this halo.…”
Section: Aq-dmentioning
confidence: 83%
“…To understand the reason behind this, we need to consider the assembly history of the structure around Aq-D. Vera-Ciro et al (2011) studied in detail the evolution of the dark matter halo surrounding the Aquarius galaxies. In the case of Aq-D, they found that until redshift of z ≈ 0.75, most of the material infall occurred along the primary filament this halo was situated on.…”
Section: Aq-dmentioning
confidence: 99%